In silico and in vitro screening of pyrrole-based Hydrazide-Hydrazones as novel acetylcholinesterase inhibitors - Emilio Mateev; Ali Irfan; Alexandrina Mateeva; Magdalena Kondeva-Burdina; Maya Georgieva; Alexander Zlatkov (Pensoft Publishers, 2024)
Virtual screening is emerging as a highly applied technique and gained prominence as widely used method for the search and identification of potential hits, significantly reducing the time needed to discover novel and effective compounds compared to high-throughput screening. Recently, the superiority of simulations with multiple programs compared to a single software docking has been discussed. The aim of this work was to apply consensus docking, molecular mechanics/generalized Born surface area (MM/GBSA) free binding energy recalculations, and in vitro evaluations on an in-house dataset of recently synthesized pyrrole-based hydrazide-hydrazones in the search for novel acetylcholinesterase (AChE) inhibitors. Two licensed softwares - GOLD 5.3 and Glide, were employed for the virtual screenings, and several chemotherapeutic potential hits were identified. Furthermore, MM/GBSA free binding energy recalculations were provided to enhance the robustness of the in silico results. The MM/GBSA scores of the top ten pyrrole-based hydrazide-hydrazones were ranging from -60.44 to -70.93 Kcal/mol. Subsequent, in vitro evaluations of the top ranked compounds revealed that 12d exhibited the highest AChE inhibitory activity, with a 55% inhibition rate at a concentration of 10 μM. Moreover, this prominent pyrrole-based AChE inhibitor formed stable complex with the active site of the enzyme. Interactions with the active amino residues Tyr72 and Tyr286 indicated that 12d was located near the peripheral anionic site of the enzyme. Additionally, in silico ADME investigations using QikProp demonstrated that 12d possesses optimal pharmacokinetic properties. In conclusion, this study identified a novel pyrrole-based AChE inhibitor 12d through a combination of computational and experimental findings.